Leaf-Impression and Palaeoscientific Study of Siwalik-belt of Koilabas in Western Nepal: Part-1 - Neetu Chandra , Pateshwari Prasad Tripathi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The present study comprises of well-preserved leaf-impression of eleven species of angiosperm. These leaf-impressions were searched from Siwalik belt of Koilabas in Western Nepal. We have found that above eleven species belonging to eleven genera and eight family of dicotyledon. Based on above study alongwith already known data, the palaeoecology and phytogeography of area shows Miocene-Pleistocene age in the Himalayan foot hills. Above study also signify the physiogenomic characters of fossil?s leaves with climate.